2017
DOI: 10.1016/j.jccase.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Late perforation of a passively fixated pacemaker lead through the right ventricle. A report and review of literature

Abstract: Lead perforation is one of the serious complications associated with cardiac pacemakers and implantable cardiac defibrillators. Late perforationsoccurring more than one month after placementare exceedingly rare and are usually more associated with actively fixed leads rather than passively fixed tined leads. We present a case of blunt ended tined lead perforation after 4 months of implantation managed by a two-step hybrid minimally invasive approach consisting of mini-thoracotomy and lead tip transection, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…2 Many authors have reported cases of lead perforation managed successfully by a surgical approach. [18][19][20] Alternatively, many case series (with numbers ranging from 3 to 31) suggest that the perforated lead may be safely removed percutaneously with surgical backup, consistent with our current results. 1,3,4,12,21,22 The complete procedural success rate reported in these series was 92% to 96%, which is comparable with our reported rate.…”
Section: Management Strategysupporting
confidence: 86%
See 1 more Smart Citation
“…2 Many authors have reported cases of lead perforation managed successfully by a surgical approach. [18][19][20] Alternatively, many case series (with numbers ranging from 3 to 31) suggest that the perforated lead may be safely removed percutaneously with surgical backup, consistent with our current results. 1,3,4,12,21,22 The complete procedural success rate reported in these series was 92% to 96%, which is comparable with our reported rate.…”
Section: Management Strategysupporting
confidence: 86%
“…According to a consensus endorsed by the American Heart Association, surgical removal of the perforated leads should be the preferred strategy . Many authors have reported cases of lead perforation managed successfully by a surgical approach . Alternatively, many case series (with numbers ranging from 3 to 31) suggest that the perforated lead may be safely removed percutaneously with surgical backup, consistent with our current results .…”
Section: Discussionmentioning
confidence: 57%
“…The degree of slack on the lead may also be an important risk factor for perforation . The clinical presentations of late perforation may vary: totally asymptomatic, chest pain, hiccup, muscle twitching, syncope, hemopneumothorax, rib perforation, and pericardial tamponade . Changes in the QRS morphology and/or loss of capture or sensing as in this case may lead to correct diagnosis; however, these electrophysiological abnormalities may be absent .…”
Section: Discussionmentioning
confidence: 92%
“…Fibrosis around the lead tip increases the risk of tissue damage with transvenous extraction. 9 Severe RV damage by the CIED lead tip is more likely to be fatal, requiring emergency surgery in many cases because of the risk of death from tamponade. Therefore, we were concerned that delayed timing of perforation (>1 month) and the use of an active‐fixation lead would require surgical extraction.…”
Section: Discussionmentioning
confidence: 99%
“…However, when tined leads perforate the myocardium and possibly the pericardium, there is a major concern that the bulky tip of the lead can damage tissues during removal. Fibrosis around the lead tip increases the risk of tissue damage with transvenous extraction 9 . Severe RV damage by the CIED lead tip is more likely to be fatal, requiring emergency surgery in many cases because of the risk of death from tamponade.…”
Section: Discussionmentioning
confidence: 99%